Numerical investigation of multiphase blood flow coupled with lumped parameter model of outflow. Issue 1 (7th November 2019) - Melka, Bartlomiej; Adamczyk, Wojciech P.; Rojczyk, Marek; Nowak, Marcin L.; Gracka, Maria; Nowak, Andrzej J.; Golda, Adam; Bialecki, Ryszard A.; Ostrowski, Ziemowit
Abstract : Purpose: The purpose of this paper is the application of the computational fluid dynamics model simulating the blood flow within the aorta of an eight-year-old patient with Coarctation of Aorta. Design/methodology/approach: The numerical model, based on commercial code ANSYS Fluent, was built using the multifluid Euler–Euler approach with the interaction between the phases described by the kinetic theory of granular flow (KTGF). Findings: A model of the blood flow in the arches of the main aorta branches has been presented. The model was built using the multifluid Euler–Euler approach with the interaction between the phases described by the KTGF. The flow and pressure patterns, as well as the volumetric concentration of the blood components, were calculated. The lumped parameter model was implemented to couple the interaction of the computational domain with the remaining portion of the vascular bed. Originality/value: The multiphase model based on the Euler–Euler approach describing blood flow in the branched large vessel with a three-element Windkessel model in the coarcted geometry was not previously described in the literature.